Inside Cover: Selective Electrochemical Reduction of Carbon Dioxide to Ethanol on a Boron‐ and Nitrogen‐Co‐doped Nanodiamond (Angew. Chem. Int. Ed. 49/2017). Issue 49 (6th November 2017) - Liu, Yanming; Zhang, Yujing; Cheng, Kai; Quan, Xie; Fan, Xinfei; Su, Yan; Chen, Shuo; Zhao, Huimin; Zhang, Yaobin; Yu, Hongtao; Hoffmann, Michael R.
Abstract : The selective reduction of CO 2 to ethanol at a B‐ and N‐co‐doped nanodiamond electrode is reported by X. Quan et al. in their Communication onpage 15607 ff. The electrode is highly active for the production of ethanol with a high Faradaic efficiency of 93.2 %. The uncovered factors for tailoring the ethanol selectivity and CO2 reduction mechanism are valuable for converting CO2 into multicarbon fuels.